2021
DOI: 10.1177/11782234211020242
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Togolese Women: Imaging and Clinicopathological Findings

Abstract: Background: Breast cancer is the most common cancer in women, and its incidence and mortality rates are expected to increase significantly over the next few years, particularly in developing countries. The aim of this study was to describe the epidemiological, clinical, radiological, histopathological, and prognostic aspects of breast cancer in Togo. Materials and methods: We retrospectively analyzed at our Department of Pathology of Lomé all cases of breast cancer in women confirmed by histology over a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Lamien-Sanou et al 14 also found a predominance of the triple-negative subtype in 29.41%. Darré et al 30 found a predominance of the Luminal B subtype (40.85%) in the general Togolese female population, with the triple-negative subtype representing only 14.08%. According to the literature, Luminal B tumors tend to be slightly more frequent and triple-negative HER2-enriched tumors appear more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Lamien-Sanou et al 14 also found a predominance of the triple-negative subtype in 29.41%. Darré et al 30 found a predominance of the Luminal B subtype (40.85%) in the general Togolese female population, with the triple-negative subtype representing only 14.08%. According to the literature, Luminal B tumors tend to be slightly more frequent and triple-negative HER2-enriched tumors appear more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Mereka berharap tindakan tersebut akan membuat benjolan tersebut mengecil bahkan hilang. Padahal tindakan memijat benjolan berpotensi mengakibatkan kerusakan lebih lanjut pada jaringan payudara Hingga 29% kasus kanker mengalami keterlambatan diagnosis 13 . Wanita tidak mencari pertolongan medis sampai mereka mencapai tahap kritis.…”
unclassified